2013
DOI: 10.1371/journal.pone.0072886
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria Localize to the Cleavage Furrow in Mammalian Cytokinesis

Abstract: Mitochondria are dynamic organelles with multiple cellular functions, including ATP production, calcium buffering, and lipid biosynthesis. Several studies have shown that mitochondrial positioning is regulated by the cytoskeleton during cell division in several eukaryotic systems. However, the distribution of mitochondria during mammalian cytokinesis and whether the distribution is regulated by the cytoskeleton has not been examined. Using live spinning disk confocal microscopy and quantitative analysis of mit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 97 publications
1
39
0
Order By: Relevance
“…RAL-induced fission of mitochondria in mitosis has very recently been proposed to contribute to their partitioning at cell division [36]. Although a recent paper [37] reported that mitochondria were recruited to the cleavage furrow during cytokinesis in HeLa and other cell types, a process its authors concluded was dependent on microtubules but not actin, we never observed this in our experiments (see, for example, Figures 3 and 4A; Figures S3A and S3D; Movie S1). …”
Section: Resultsmentioning
confidence: 99%
“…RAL-induced fission of mitochondria in mitosis has very recently been proposed to contribute to their partitioning at cell division [36]. Although a recent paper [37] reported that mitochondria were recruited to the cleavage furrow during cytokinesis in HeLa and other cell types, a process its authors concluded was dependent on microtubules but not actin, we never observed this in our experiments (see, for example, Figures 3 and 4A; Figures S3A and S3D; Movie S1). …”
Section: Resultsmentioning
confidence: 99%
“…Indeed, while mitochondria congress towards the division plane from anaphase to early cytokinesis, presumably to deliver ATP for the contraction of the actomyosin ring [5], in late cytokinesis/early G 1 , mitochondria are transported away from the division plane and spread towards the periphery of the two daughter cells [4]. This latter phenomenon is dependent on Miro's interaction with a cell-cycle-specific cytoskeletal adaptor, the centromeric protein F (Cenp-F).…”
Section: Mitochondrial Transport During Mitosismentioning
confidence: 99%
“…Thus steering mitochondria close to ATP demanding sites during mitosis (e.g. the actomyosin ring [5]) might be physiologically relevant.…”
Section: Mitochondria and Mitosis -Mechanism And Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, for passive inheritance to occur, mitochondria must also release from cytoskeletal anchors and distribute evenly throughout the cytoplasm, which fragmentation alone does not guarantee (Mishra and Chan, 2014). Conflicting reports have implicated microtubules and actin as active drivers of mitochondrial inheritance, but it remains unknown how these elements would position mitochondria during cell division (Lawrence and Mandato, 2013c; Lee et al, 2007; Rohn et al, 2014). …”
Section: Introductionmentioning
confidence: 99%